Bcl-2 expression and image analysis of premalignant and malignant colonic lesions - Sonia L. El-Sharkawy; Naglaa F. Abbas; Wafaa E. Abdelaal; Manal A. Badawi (Journal of the Arab Society for Medical Research)
Background/aim Colorectal cancer is the third malignancy worldwide with high mortality. The development of colorectal carcinoma is a multiple step process that turns normal cells into malignant ones. One of these steps is inhibiting apoptosis. Bcl-2 is the key regulators of apoptosis and thus inhibits programmed cell death. The relationship between cell death and cell proliferation is balanced through apoptosis. This study aimed to evaluate immunohistochemical bcl-2 expression, nuclear morphometric parameters, and cell cycle values in premalignant and malignant colon lesions. Material and methods Sixty colonic paraffin blocks (10 normal mucosa, 20 adenomas, and 30 carcinomas) from private laboratories and the Pathology Department, National Research Centre, Cairo, Egypt, were included in this study. Bcl-2 expression was evaluated by immunohistochemistry. Nuclear morphometric parameters and cell cycle values were studied using an image analysis system. Results Immunohistochemical results showed expression of bcl-2 in the lower half of normal colonic crypts. Bcl-2 positivity was detected in 53% of carcinomas and 85% of adenomas with significant difference. The percentage of bcl-2 positive cells in carcinomas was significantly decreased with increasing grades. In carcinomas, nuclear area showed significant increase with increasing grades. Nuclear area showed significant difference between high-grade dysplastic adenomas and carcinomas. Carcinomas showed high proportion of aneuploid cells with significant difference than adenomas. Inverse correlation was detected between aneuploidy and bcl-2 positivity. Conclusion Bcl-2 protein has a role in early event of colorectal carcinogenesis. The acceptable reliability of immunohistochemical, nuclear area, and cell cycle analysis may serve as diagnostic and prognostic indicators in benign and malignant colorectal lesions.